(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article investigates the metabolic effects of stress on neuronal structures in immobilized animal models, focusing on acute and chronic immobilization stress. Through experimental analysis, the study examines changes in neuromuscular coordination, neural metabolism, and immune response markers under conditions of physical restraint. Findings reveal significant alterations in oxidative stress levels, with elevated markers of free radical activity and disruptions in homeostasis in central neuronal structures.